Genotype-dependent DNA methylation patterns are negatively associated with allelic variation rather than heat-induced gene expression in two contrasting potato genotypes - Yeo, Darren; Eydam, Julia; Bruckmüller, Julien; Kauder, Friedrich; Lübeck, Jens; Kaier, Alexander; Sonnewald, Sophia; Sonnewald, Uwe (Plant Journal, 2026)
Potato (Solanum tuberosum L.) is an important food crop that is sensitive to high temperatures, which cause major changes in the transcriptome and a reduction in yield. In several plant species, DNA methylation has been reported to influence gene expression, particularly under abiotic stress conditions. However, the role of DNA methylation in regulating gene expression in heat-tolerant and heat-sensitive potato genotypes is still poorly understood. In this study, we conducted genome-wide DNA methylome and transcriptome analyses of leaves from two contrasting potato cultivars, Annabelle (moderately heat-tolerant) and Camel (heat-sensitive), before and after heat stress (HS). Genome-wide differential methylation analysis revealed that most identified differentially methylated regions (DMRs) were constitutive, reflecting variation between cultivars rather than being induced by HS. While thousands of heat-responsive differentially expressed genes (DEGs) were identified, only a small fraction coincided with heat-induced DMRs. Despite substantial constitutive DNA methylation and transcriptome differences between the cultivars, we found no consistent association between DMRs and DEGs, indicating that DNA methylation does not play a widespread direct regulatory role in gene expression. Surprisingly, hypermethylated genomic regions were associated with lower alternative allele frequencies, whereas hypomethylated regions showed the opposite trend. These findings indicate that the potato DNA methylome is largely stable under HS and that constitutive DNA methylation variation contributes rather to genetic diversity than to the direct regulation of gene expression.
CRIS-Team Scopus Importer:2026-01-30
Keywords: allelic variation; DNA methylation; heat stress; potato

SELF-PRUNING 6A promotes tuberization and heat tolerance but lowers immunity of potato (Solanum tuberosum L.) - Yeo, Darren; Eydam, Julia; Koch, Lisa; Lackus, Nathalie D.; Reinert, Stephan; Kauder, Friedrich; Bruckmüller, Julien; Lübeck, Jens; Sonnewald, Sophia; Sonnewald, Uwe (Journal of Experimental Botany, 2025)
Potato (Solanum tuberosum L.) is a crucial global food crop, but high temperatures inhibit tuberization and reduce yield. To investigate heat tolerance genetics, a crossing population was created using the cultivars Annabelle (early tuber-forming, moderately heat tolerant) and Camel (mid-early tuber-forming, heat-sensitive). Screening over 500 progenies identified 10 contrasting individuals for further study. RNA-Seq analysis of parents and selected progeny confirmed the phenotypic heat tolerance classification. Tolerant genotypes exhibited earlier tuberization and significantly higher leaf expression of SELF-PRUNING 6A (SP6A), a key tuberization gene. Gene Ontology analysis revealed that under control conditions, heat-tolerant plants showed down-regulation of multiple defense-related pathways, particularly terpene synthases, leading to reduced terpene accumulation. This correlated with a diminished immune response, evident from lower ethylene production upon flgII-28 treatment. To explore the role of SP6A in the observed trade-off between tuberization and defense, transgenic SP6A overexpressing plants were studied. Like heat-tolerant progeny, SP6A overexpression led to down-regulation of defense genes, reduced terpene accumulation, and a weaker immune response. These findings suggest that SP6A-mediated assimilate redistribution plays a key role in the negative correlation between early tuberization and pathogen defense, providing insights into the genetic mechanisms underlying heat tolerance in potatoes.
CRIS-Team Scopus Importer:2025-12-26
Keywords: earliness; heat; immunity; potato; SP6A; stress tolerance; terpenes